Rouhani’s and Obama’s Persian New Year messages: A systemic functional grammar perspective - Karimnia Amin; Rahbarian Shidak (ExELL (Explorations in English Language and Linguistics))
This study investigated Nowruz (Persian New Year) messages by Presidents Hassan Rouhani and Barack Obama in March 2016. The study critically analyzed the discourse of these two presidential messages and uncovered the hidden aspects of their ideologies, policies, and background worldviews. In doing so, an integrated version of Halliday’s systemic functional grammar (SFG) and critical discourse analysis (CDA) was used. The analysis of data included various linguistic dimensions (e.g. processes, modality, transitivity) of the messages and their statistics. Although results suggested that Obama intended to build a more intimate situation, both presidents tried to inspire a spirit of action, development and effort in their respective governments. The messages did not reveal considerable thematic differences, except some discoursal religious features expressed in Rouhani’s message.